Characteristics and outcomes of SARS-CoV-2 breakthrough infections among double-vaccinated and triple-vaccinated patients with inflammatory rheumatic diseases - Hasseli-Fräbel, Rebecca; Richter, Jutta; Hoyer, Bimba Franziska; Lorenz, Hanns-Martin; Pfeil, Alexander; Regierer, Anne C.; Schmeiser, Tim; Strangfeld, Anja; Voll, Reinhard; Krause, Andreas; Reckert, Sabine; Gräßler, Anett; et al. (RMD Open, 2023)
Objective: To analyse the clinical profile of SARS-CoV-2 breakthrough infections in at least double-vaccinated patients with inflammatory rheumatic diseases (IRDs). - Methods: Data from the physician-reported German COVID-19-IRD registry collected between February 2021 and July 2022 were analysed. SARS-CoV-2 cases were stratified according to patients’ vaccination status as being not vaccinated, double-vaccinated or triple-vaccinated prior to SARS-CoV-2 infection and descriptively compared. Independent associations between demographic and disease features and outcome of breakthrough infections were estimated by multivariable logistic regression. - Results: In total, 2314 cases were included in the analysis (unvaccinated n=923, double-vaccinated n=551, triple-vaccinated n=803, quadruple-vaccinated n=37). SARS-CoV-2 infections occurred after a median of 151 (range 14-347) days in patients being double-vaccinated, and after 88 (range 14-270) days in those with a third vaccination. Hospitalisation was required in 15% of unvaccinated, 8% of double-vaccinated and 3% of triple-vaccinated/quadruple-vaccinated patients (p<0.001). Mortality was 2% in unvaccinated, 1.8% in the double-vaccinated and 0.6% in triple-vaccinated patients. Compared with unvaccinated patients, double-vaccinated (OR 0.43, 95% CI 0.29 to 0.62) and triple-vaccinated (OR 0.13, 95% CI 0.08 to 0.21) patients showed a significant lower risk of COVID-19-related hospitalisation. Using multivariable analysis, the third vaccination was significantly associated with a lower risk for COVID-19-related death (OR 0.26; 95% CI 0.01 to 0.73). - Conclusions: Our cross-sectional data of COVID-19 infections in patients with IRD showed a significant reduction of hospitalisation due to infection in double-vaccinated or triple-vaccinated patients compared with those without vaccination and even a significant reduction of COVID-19-related deaths in triple-vaccinated patients. These data strongly support the beneficial effect of COVID-19 vaccination in patients with IRD. - Trial registration number EuDRACT 2020-001958-21.
Gesehen am 26.06.2023